Constructivism Learning in Learning Moral Beliefs at SMK 1 Muhammadiyah School Yogyakarta - Supratama, Riky; Indahsari , Henik Nur; Wahyuni, Dina Auliatil; Nazalia, Izza; Dewi Fadilah, Hanura (PT Mutiara Bustan Ilmu, 2025)
This research aims to explore the implementation of Constructivism Theory in the teaching of Aqidah Akhlak at SMK Muhammadiyah 1 Yogyakarta. Through qualitative methods including interviews and documentation reviews, this study explores how teachers apply Constructivism Theory to improve student engagement and learning outcomes. The findings revealed that when teachers apply Constructivism Theory, students become more actively involved in the learning process, resulting in a dynamic and interactive classroom environment. The implementation of this constructivism theory also faces challenges. Challenges arise when students are apathetic or unresponsive, thus hindering the realization of the full benefits of theory. The study highlights the importance of aligning educational theory with classroom practice in Islamic education and offers insights for improving teaching methods in Islamic schools.